Synthesis, Characterization and Antimicrobial Activity of 3-Acetyl-4-hydroxy-6-methyl-(2H)pyran-2-one Schiff Base with 2,2'-(Ethylenedioxy)diethylamine and its Co(II), Ni(II) and Cu(II) Complexes - N. Asegbeloyin, Jonnie; Babahan, IIknur; N. Ukwueze, Nwanneka; S. Oruma, Uchechukwu; Coban Poyrazoglu, Esin; F. Eze, Uchenna; Biyik, Halil (Asian Journal of Chemistry, 2015)
A Schiff base was synthesized by the interaction of 3-acetyl-4-hydroxy-6-methyl-(2H)pyran-2-one with 2,2'-(ethylenedioxy)diethyl-amine in ethanolic medium. The ligand was characterized on the basis of elemental analysis, infrared, 1H and 13C NMR spectra. Cobalt(II), Ni(II) and Cu(II) complexes of the type ML(H2O)2 were prepared by interaction of the metal(II) halides with hot ethanolic solution of the Schiff base. The complexes were characterized by elemental analysis, molar conductance, magnetic measurements, infrared and electronic spectral studies. Results show that the ligand behaved as dibasic tetradentate molecule, coordinating via imino nitrogens and the enolic oxygens, to form six-coordinate octahedral metal complexes. The compounds were screened for in vitro antimicrobial activity against some bacteria and yeasts. Results showed that some of the compounds are active against few microbes.